Chronic Lumbar Spondylolysis in an Adolescent Hockey Player. Issue 4 (October 2018) - Sivanich, Ashley; Shultz, John; Raja, Avais
Abstract : Lumbar spondylolysis is an underreported condition in adolescents who play the sport of ice hockey. Managing spondylolysis in a growing adolescent proves to be challenging in regard to sport restrictions and return to play. Advanced imaging, including magnetic resonance imaging (MRI) or single-photon emission computed tomography (SPECT), should be acquired in order to reach a faster definitive diagnosis. Some cases may lead to a chronic form of spondylolysis that requires patience from the provider, the patient, and the patient's family.